Susceptibility of Hamsters to Clostridium difficile Isolates of Differing Toxinotype - Buckley, Anthony M.; Spencer, Janice; Maclellan, Lindsay M.; Candlish, Denise; Irvine, June J.; Douce, Gillian R. (PLOS ONE, 2013)
Clostridium difficile is the most commonly associated cause of antibiotic associated disease (AAD), which caused ∼21,000 cases of AAD in 2011 in the U.K. alone. The golden Syrian hamster model of CDI is an acute model displaying many of the clinical features of C. difficile disease. Using this model we characterised three clinical strains of C. difficile, all differing in toxinotype; CD1342 (PaLoc negative), M68 (toxinotype VIII) & BI-7 (toxinotype III). The naturally occurring non-toxic strain colonised all hamsters within 1-day post challenge (d.p.c.) with high-levels of spores being shed in the faeces of animals that appeared well throughout the entire experiment. However, some changes including increased neutrophil influx and unclotted red blood cells were observed at early time points despite the fact that the known C. difficile toxins (TcdA, TcdB and CDT) are absent from the genome. In contrast, hamsters challenged with strain M68 resulted in a 45% mortality rate, with those that survived challenge remaining highly colonised. It is currently unclear why some hamsters survive infection, as bacterial & toxin levels and histology scores were similar to those culled at a similar time-point. Hamsters challenged with strain BI-7 resulted in a rapid fatal infection in 100% of the hamsters approximately 26 hr post challenge. Severe caecal pathology, including transmural neutrophil infiltrates and extensive submucosal damage correlated with high levels of toxin measured in gut filtrates ex vivo. These data describes the infection kinetics and disease outcomes of 3 clinical C. difficile isolates differing in toxin carriage and provides additional insights to the role of each toxin in disease progression.